The Use of Augmented Reality in Science Education in Elementary Schools: A Systematic Literature Review - Urifah, Firda Nur; Fitrasari, Nisfi Laila; Ramadhani, Qurrota A’yun; Afrina, Nabila Nur; Rohmah, Nur Lia Selviatur; Kamila, Anisa Fitri (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to identify the use of Augmented Reality (AR) in science education at the elementary school level through a systematic review of published research. The study examines AR-based learning designs, classroom implementation, and its effects on conceptual understanding, learning motivation, and student engagement. A Systematic Literature Review method was employed through identification, selection, and thematic analysis of eligible articles. The findings reveal that AR enhances student engagement, clarifies abstract concepts, and supports exploratory learning activities. In addition, AR provides interactive learning experiences that contribute to improved learning outcomes. The study concludes that AR plays a significant role in strengthening science learning in elementary schools and has strong potential for broader application in educational practice.